Studi Komparasi Antara Guru Penerima Tunjangan Profesi Guru (TPG) dan Guru Penerima Tunjangan Kinerja (TuKin) terhadap Semangat Kerja di MAN 01 Kepahiang - Aziz, Toher; Warlizasusi, Jumira; Nasution, Aida Rahmi (Cakrawala Journal is a scientific journal published by Nahdlatul Ulama Islamic Institute (IAINU) Kebumen. This journal focuses on the Islamic Education Management Study and Social Studies which is published twice a year.IAINU Kebumen, 2024)
This study aims to analyze the comparison between Teachers who receive a Teacher's Professional Benefit (TPG) and teachers who are receiving a performance benefit (TuKin) against the spirit of work in MAN 01 Kepahiang. The research methods used are quantitative comparative studies with data collection techniques through interviews, observations, documentation, and quizzes. Teachers serve as the leading guardians in the education system and are an important and strategic component. Because they are directly involved in the teaching learning process and are a vital part of the educational system as a whole, teachers are vital for improving the quality of education. The granting of Teacher Profession Benefits (TPG) and Performance Benefit (TuKin) is expected to enable teachers to be more enthusiastic in carrying out their basic duties and functions, so as to get maximum results and improve the quality of education in Indonesia. The results of the study showed that from the results of hypothesis test / T test obtained average value of the work spirit of the teacher beneficiary of the profession benefit = 0.274 while Teacher Beneficiary performance benefit = 0,275 Average value of work spirit for both groups is very close to the difference of only 0.001 this suggests that in general the value of working spirit between the two groups is almost the same and has no significant difference. It shows that the allowance between the two groups of teachers has both had an impact on each other's work spirit in addition to other factors that can influence the work spirit.